Witold Gombrowicz: el problema de la identidad de un escritor polaco en el exilio - Matyjaszczyk Grenda, Agnieszka (Revista de Filología Románica, 2002)
The work of Gombrowicz constitutes an universal literary patrimony, however it would be inconceivable not to associate it to the tradition literary Pole, and from this Transatlantic point of view it is a dialectical bereavement with the tradition of Mickiewicz and Sienkiewicz of the Polish literature. Another work of Gombrowicz, the work Operetta, mentions visibly and in a critical way to other works literary previous Poles as the consecrated works of Krasin´ski The Nodivine Comedy and The wedding of the modernist Wyspian´ski. In their Notes that are the writer´s intimate notes in smaller measure, and that rahter they constitute a long rehersasla on the culture and the civilization in general, Gombrowicz in a particularly wide way, treats the topic of the homelan, of how a Pole perceives it, of the national defects ant the cultural myths that stigmatize to the Polish town.